Metformin use and cardiovascular events in patients with type 2 diabetes and chronic kidney disease. Issue 5 (4th March 2019) - Charytan, David M.; Solomon, Scott D.; Ivanovich, Peter; Remuzzi, Giuseppe; Cooper, Mark E.; McGill, Janet B.; Parving, Hans‐Henrik; Parfrey, Patrick; Singh, Ajay K.; Burdmann, Emmanuel A.; Levey, Andrew S.; Eckardt, Kai‐Uwe; et al.
Abstract : Aims: Metformin could have benefits on cardiovascular disease and kidney disease progression but is often withheld from individuals with diabetes and chronic kidney disease (CKD) because of a concern that it may increase the risk of lactic acidosis. Materials and methods: All‐cause mortality, cardiovascular death, cardiovascular events (death, hospitalization for heart failure, myocardial infarction, stroke or myocardial ischemia), end stage renal disease (ESRD) and the kidney disease composite (ESRD or death) were compared in metformin users and non‐users with diabetes and CKD enrolled in the Trial to Reduce Cardiovascular Events with Aranesp (darbepoeitin‐alfa) Therapy (TREAT) (NCT00093015). Outcomes were compared after propensity matching of users and non‐users and in multivariable proportional hazards models. Results: There were 591 individuals who used metformin at baseline and 3447 non‐users. Among propensity‐matched users, the crude incidence rate for mortality, cardiovascular mortality, cardiovascular events and the combined endpoint was lower in metformin users than in non‐users, but ESRD was marginally higher (4.0% vs 3.6%). Metformin use was independently associated with a reduced risk of all‐cause mortality (HR, 0.49; 95% CI, 0.36‐0.69), cardiovascular death (HR, 0.49; 95% CI, 0.32‐0.74), the cardiovascular composite (HR, 0.67, 95% CI, 0.51‐0.88) and the kidney disease composite (HR, 0.77; 95% CI, 0.61‐0.98). Associations with ESRD (HR, 1.01; 95% CI, 0.65‐1.55) were not significant. Results were qualitatively similar in adjusted analyses of the full population. Two cases of lactic acidosis were observed. Conclusions: Metformin may be safer for use in CKD than previously considered and may lower the risk of death and cardiovascular events in individuals with stage 3 CKD.